Do arbuscular mycorrhizal fungi recolonize revegetated grasslands?. (January 2014) - Gibson‐Roy, Paul; McLean, Cass; Delpratt, John C.; Moore, Greg
Summary Fifteen native and common exotic herbaceous species from four functional groups (C4 grass, C3 grass, chamaephyte and hemicryptophyte) occurring within remnant and revegetated grassland and grassy woodlands were sampled for evidence of structures associated with functioning arbuscular mycorrhizal fungi (AMF) from across a broad geographical range of central and south‐western Victoria, Australia. Revegetated communities had been established on ex‐agricultural land by direct seeding. They included sites that had been kept fallow with herbicide for up to 3 years prior to seeding and those from which topsoil had been removed (scalped) to a depth of 100 mm prior to seeding. Structures associated with AMF (external and internal aseptate hyphae, arbuscules and vesicles) were observed in root samples from all native and exotic species, regardless of site history (remnant or revegetated; fallowed or scalped). These findings indicate that AMF are ubiquitous in the herbaceous flora of this region (native and exotic), even in situations where sites had been intensively disturbed prior to revegetation treatment. However, while there was evidence of AMF in all revegetated communities, only sites which had been scalped prior to direct seeding supported species‐rich native herbaceous communities.